RATIO LEGIS REQUIREMENTS FOR SENIOR HIGH SCHOOL EDUCATION (SMA) OR THE EQUIVALENT FOR PRESIDENTIAL CANDIDATES AND VICE PRESIDENTIAL OF THE REPUBLIC OF INDONESIA - Reza Guritna Hutama; Muchamad Ali Safa’at; Indah Dwi Qurbani (RADJA PUBLIKA, 2023)
The purpose of this research is to understand and analyze the ratio legis setting the minimum education requirements for senior high school or its equivalent for a presidential candidate from the study of treatises on discussing educational needs as well as to find out the conditions that can be used in determining the ability of a presidential candidate. The research method used by the author is a normative legal research method, by researching principles, synchronization, systematics, and legal comparisons. The author uses this type of normative legal research because, in formulating the problem, the author emphasizes the legal ratio to the educational requirements of a presidential candidate in Law No. 7 of 2017 concerning General Elections. This is influenced by the emergence of the author's curiosity about reasoning (ratio legis) from the minimum requirements for senior high school school or the equivalent for presidential candidates in Law No. 7 of 2017 concerning General Elections. The Indonesian House of Representatives is expected to be able to reformulate the development of regulations on educational requirements for presidential and vice-presidential candidates in Indonesia. The burden of duties carried out by a president certainly requires more ability to carry out the mandate that the people have entrusted to him in leading the running of the government. In this case, education is one of the components to assess a president's competence and ability.